Optimization of The use of Wireless Lan Devices to Minimize Operational Costs - Achmad Rian Tarmizi; Ahmat Adil; Lilik Widyawati (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2020)
WLAN technology has been widely developed for the needs of internet access in people's lives. Several generations of WLAN technology include IEEE 802.11b, IEEE 802.11a, IEEE 802.11g and IEEE 802.11n. At the STAHN Rectorate Building, Gde Pudja Mataram, WLAN technology in its application requires financial consideration because excessive use of Internet Service Provider services results in a waste of operational costs. The application of WLAN is still not optimal, because there are not too many users, but the operational costs of implementing the local wireless network are very large, due to less optimal application of network infrastructure. The recommended WLAN technology is IEEE 802.11n, while the technology is the latest technology that has better quality than the previous generation technology. The research methodology uses the Network Development Life Cycle (NDLC). Of the 6 stages available, only 3 stages are used, namely Analysis, Design and Simulation of Prototyping. The results obtained from this study are models that design a WLAN that suits your needs, and complements the entire Building area. Optimization has succeeded in reducing the need for ISP and client services while still being able to enjoy services as needed and cost optimization can be reduced by around 28%.